Association between the students’ Self-Renewal Capacity and Advanced Mathematical Thinking - Suryana, Andri (Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai-Nilai Islami); Vol 1 No 1 (2017): Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai Islami ), 2017)
The purpose of this research is to determine the correlation between the students’ Self-Renewal Capacity and Advanced Mathematical Thinking. This research is a quantitative research with survey method. The subjects in this research were students of Mathematics Education who contracted Mathematical Statistics Course in one of the private universities in East Jakarta. Sampling technique used purposive sampling. This research used various main instruments. They were Self-Renewal Capacity (SRC) scale and test of Advanced Mathematical Thinking (AMT). The results of this research is: there is enough association between the students’ Self-Renewal Capacity and Advanced Mathematical Thinking .